Household food insecurity is not associated with BMI for age or weight for height among Brazilian children aged 0-60 months - Kac, G; Schlüssel, M; Pérez-Escamilla, R; Velásquez-Melendez, G; Da Silva, A (Public Library of Science, 2012)
We examined the association between Household Food Insecurity (HFI), weight for height z-score (WHZ) and Body Mass Index for age z-score (BMI-Z) in a representative sample of children 0-60 months of age (n = 3,433) in five Brazilian geographical regions. Data were derived from the 2006-07 Brazilian Demographic and Health Survey. HFI was measured with the Brazilian Food Insecurity Scale. Associations were estimated using multiple linear regression models (β coefficients and 95% CI) taking into account the complex sampling design. Interaction terms between HFI and geographical region and HFI and child sex and child age were assessed. The weighted prevalence of any level of HFI was 48.6%. Severe food insecurity was more prevalent among children from the North region (16.8%), born from mothers with <4 years of schooling (15.9%) and those from families with ≥3 children (18.8%). The interaction between HFI and geographical region was non-significant for BMI-Z (P = 0.119) and WHZ (P = 0.198). Unadjusted results indicated that HFI was negatively associated with BMI-Z (moderate to severe HFI: β = -0.19, 95% CI: -0.35 - -0.03, P = 0.047), and WHZ (moderate to severe HFI: β = -0.26, 95% CI: -0.42 - -0.09, P = 0.009). Estimates lost significance after adjustments for key confounders such as mothers' skin color, mothers' years of schooling, place of household, household income quartiles, mothers' smoking habit, mothers' marital status, number of children 0-60 months in the household, and birth order. HFI is unrelated to weight outcomes among Brazilian children 0-60 months.